KESEJAHTERAAN SEKOLAH DITINJAU DARI ORIENTASI BELAJAR MENCARI MAKNA DAN KEMAMPUAN EMPATI SISWA SEKOLAH MENENGAH ATAS - Setyawan, Imam; Dewi, Kartika Sari (Jurnal Psikologi, 2015)
Education evaluation should be based on studentsâ€™ viewpoints and interest. Based on that, the research was aimed to determine the importance of purpose oriented study and ability to show empathy to the school well- being. The proposed hypothesis was there is positive correlation between purpose-oriented study and ability to show empathy to the school well-being. The study involved 123 senior high school students based on simple random sampling method. Data were collected using the School Well-being Scale (20 items, Î± = .81), theÂ Purpose-Oriented Study Scale (20 items; Î± = .77) and the Empathy Scale (24 items; Î± = .79). Regression analysis was used to test the hypothesis. The result shows that there is a significant and positive correlation betweenpurpose-oriented study and ability to show empathy to the school well-being (r = .364; p < .001). It emphasizes the importance of using tolerated interactional teaching-learning process so that the students will be able to obtain learning meanings that are attached to the school environment.